2022
DOI: 10.1111/hex.13479
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a codesign process with young people to prioritize outcomes for a systematic review of interventions to prevent self‐harm and suicide

Abstract: Background: Research and clinical outcomes that matter to people with lived experience can significantly differ from those outcomes studied by researchers. To inform a future Cochrane review of suicide and self-harm prevention interventions, we aimed to work with young people with relevant lived experience to agree on priority outcomes.Design: Four participatory codesign workshops were completed across two sites (New Zealand, United Kingdom) with 28 young people in total. We iteratively adapted the methods ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…Skilled facilitation, and time and resources to do this well were identified as key to the success of the group. This echoes an emerging literature on the importance of facilitation in effective public involvement, including as a catalyst for discussion, reflection and relationship building [ 15 ] and in the process of providing feedback [ 17 ]. But investment in facilitation, as well as recognition of the skills and expertise involved, is also essential [ 37 ].…”
Section: Discussionsupporting
confidence: 58%
“…Skilled facilitation, and time and resources to do this well were identified as key to the success of the group. This echoes an emerging literature on the importance of facilitation in effective public involvement, including as a catalyst for discussion, reflection and relationship building [ 15 ] and in the process of providing feedback [ 17 ]. But investment in facilitation, as well as recognition of the skills and expertise involved, is also essential [ 37 ].…”
Section: Discussionsupporting
confidence: 58%
“…Participants also report experiencing both positive (e.g., self‐understanding, helping others, and interest) and negative (e.g., personal experiences, awareness of others' suffering) experiences taking part in mental health research (Hasking et al, 2015). These findings support recent calls for greater inclusion of people with NSSI lived experience in all aspects of the research process (Knowles et al, 2022; Lewis & Hasking, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Contrastingly, those who have participated in therapeutic interventions for self‐harm consistently report that reduction in frequency of typical self‐harming behaviours are alone, not enough to indicate improvement to their lives and mental well‐being (Owens et al, 2020). Likewise, research concerning client's treatment outcome priorities for self‐harm interventions found that reducing self‐harm was a lower priority compared to other outcomes such as establishing a safer or more accepting environment for disclosure (Knowles et al, 2022). This study found that when the therapy requires patients to confront or eradicate self‐harming behaviours before trust has been established, a conflict can occur within the therapeutic relationship that can lead patients to withhold information or disengage from the therapy.…”
Section: Discussionmentioning
confidence: 99%